2018
DOI: 10.1016/j.jogn.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Thematic Analysis of Women's Perspectives on the Meaning of Safety During Hospital-Based Birth

Abstract: Physical and emotional safety are inextricably embedded in the patient experience, yet this connection may be overlooked in some inpatient birth settings. Clinicians should be mindful of how the birth environment and their behaviors in it can affect a woman's feelings of safety during birth. Human connection is especially important during risk moments, which represent a liminal space at the intersection of physical and emotional safety. At least one team member should focus on the provision of emotional suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Gathering the opinions of women and families, while beyond the scope of this particular study, is something that our Safety Learning Laboratory for Neonatal and Maternal Care is committed to investigating. 29 Our work was limited in several other ways. Because our team included clinicians who work in labor and delivery units, we acknowledge our experience may have influenced the questions we asked during site visits and the problems we may have been primed to find.…”
Section: Discussionmentioning
confidence: 99%
“…Gathering the opinions of women and families, while beyond the scope of this particular study, is something that our Safety Learning Laboratory for Neonatal and Maternal Care is committed to investigating. 29 Our work was limited in several other ways. Because our team included clinicians who work in labor and delivery units, we acknowledge our experience may have influenced the questions we asked during site visits and the problems we may have been primed to find.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal care has historically emphasized frequent in-person visits, which became a de facto source of social and emotional support for the pregnant person ( Coley et al, 2018 ; Gregory et al, 2020 ; Nicoloro-SantaBarbara et al, 2017 ). In addition, the labor and birth experience in the hospital setting often serves as the apex, magnifying the impact of nursing care on a person’s understanding of and satisfaction with their entire pregnancy experience ( Lyndon et al, 2018 ; Simon et al, 2016 ). As with many health-related transitions, pregnancy and birth is primarily a social experience in which care services support not only the medical health and well-being of patients but also the development and growth from individual to parent ( Hill et al, 2019 ; Kennedy et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our respondents reported that hospitals refused to allow them to take their placentas home, which upset them because they felt their placentas were their property and taking them was their right. Perceived patient safety during women's birthing experiences has been shown to be influenced by organizational and interpersonal interactions (Lyndon, Malana, Hedli, Sherman, & Lee, 2018). More awareness of placentophagy can help influence hospital policy and support patient autonomy.…”
Section: Discussionmentioning
confidence: 99%